2021
DOI: 10.3390/vaccines9020128
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students and SARS-CoV-2 Vaccination: Attitude and Behaviors

Abstract: Since physicians play a key role in vaccination, the initial training of medical students (MS) should aim to help shape their attitude in this regard. The beginning of vaccination programs against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an excellent time to assess the attitudes held by both medical and non-medical students regarding vaccination. A 51- to 53-item questionnaire including the Depression, Anxiety and Stress Scale was administered to 1971 students (49.21% male; 34.86% MS); t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 38 publications
9
100
5
Order By: Relevance
“…Higher willingness to vaccinate among doctors and medical students fits well with the vaccination schedule, as they belong to the group of the highest priority for vaccination in Poland [5,29]. That gives time for media campaigns that aim to convince the undecided groups until it is to be their turn.…”
Section: Willingness To Get Vaccinatedmentioning
confidence: 90%
See 2 more Smart Citations
“…Higher willingness to vaccinate among doctors and medical students fits well with the vaccination schedule, as they belong to the group of the highest priority for vaccination in Poland [5,29]. That gives time for media campaigns that aim to convince the undecided groups until it is to be their turn.…”
Section: Willingness To Get Vaccinatedmentioning
confidence: 90%
“…In our previous study that was performed on medical and non-medical students, we applied the analogous questionnaire, which was available from 22 December 2020 to 25 December 2020 [5]. Of all the groups included in the two studies, medical students and doctors were the most comparable ones.…”
Section: Comparison Between the Present And Previous Study On Medicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Adoption of vaccination practices by healthcare workers plays a key role in motivating the general population through setting of example. 8,24 Concerns regarding COVID-19 vaccine adverse events as a possible reason for hesitancy has been highlighted by most studies concerning both university students and general population. 812,17 Further, concerns regarding vaccine efficacy seen to play a role in adoption of the COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…This is since acceptance of vaccine might be more among medical students as compared to non-medical students and general population. 24 It was also found that conspiracy theories don’t tend to affect medical students as compared to non-medical students. 24 On the other hand, a study conducted in Italy found no difference between hesitancy among medical and non-medical studnets.…”
Section: Discussionmentioning
confidence: 99%